Finders, Keepers? - Niko Jaakkola; Daniel Spiro; Arthur A. van Benthem (Center for Economic Studies and ifo Institute (CESifo), 2017)
Natural-resource taxation and investment exhibit cycles in a vast number of countries, driving political turmoil and power shifts. Using a rational-expectations model, we show cycles result from governments' inability to commit to future taxes and firms' inability to credibly exit a country indefinitely. A government sets a low initial tax inducing high investments, which in turn prompts it to increase taxes next period. This induces low investment thus low future taxes, and so on. We investigate which factors reinforce cycles and present ways of avoiding them, and document cycles across many countries including detailed case studies of two Latin-American countries.
Keywords: H25; Q35; Q38; 330; resource taxation; tax cycles; limited commitment; expropriation